Passing the sacred fire after the end of aarti - Mumbai Archive Project Team (Jio Institute, 2024)
As the sacred fire is passed around, devotees wave their hands over the flame and touch their foreheads, signifying the reception of divine blessings. The light of the aarti flame is believed to purify the mind and spirit, creating a sacred atmosphere for worship.